Contributions of Chondroitin Sulfate Proteoglycans to Neurodevelopment, Injury, and Cancer - Silver, Daniel J. (2014)
Chondroitin sulfate proteoglycans (CSPGs) are a diverse family of extracellular matrix (ECM) molecules that make significant contributions to the patterning and routing of migrating neural cells and extending axons. Three distinct modes of migration mediation have been observed, which result from the relative abundance and positioning of expressed CSPGs, the profile of CSPG receptors expressed by the motile cell types, and the overall way in which the CSPGs integrate into and stabilize the neural ECM. Here we discuss recent findings that help to clarify the molecular mechanisms that underlie these distinct migration-regulating properties as they pertain to neural development, CNS injury, and gliomagenesis.